Mit – umysł – rzeczywistość. Kognitywne uwarunkowania archaicznych form narracyjnych na przykładzie mitu - Czeremski, Maciej (Poznańskie Studia Polonistyczne. Seria Literacka, 2019)
The article discusses the cognitive conditions of mythical narratives, especially their relationship with the architecture of the human mind and the processes of its evolutionary formation. The analyzed features are: a) a permanent arrangement of events (monomyth); b) a semiosis based on bricolage, and c) a counter-intuitive supernaturalism. The stability of the system of mythical events is related to the subjective significance of the elements of the chain of basic biological activities. The proposed explanation for bricolage is the embodied nature of the human mind. In combination with the archaic character of the myth, it translates tendency to code abstraction in specific objects. The presence of counter-intuitiveness in the myth is explained by the interaction between innate knowledge about ontological categories and cognitive fluidity, which allows to deformed them and the  influence of what is counter-intuitiveness on the effectiveness of the cultural transmission of narrative containing it.